Safety of idarucizumab in the reversal of dabigatran at six tertiary care Ontario hospitals. Issue 5 (7th August 2021) - Abdulrehman, Jameel; Zarabi, Sahar; Elbaz, Carolyne; de Wit, Kerstin; Lin, Yulia; Sholzberg, Michelle; Selby, Rita
Abstract: Background: Idarucizumab, a monoclonal antibody fragment that reverses the anticoagulant effect of dabigatran, was approved for use in Canada in 2016. Objective: Our objective was to assess the safety of idarucizumab among patients who received the drug within the first 3 years of its use in Canada. Patients/Methods: We performed a retrospective health records review of all idarucizumab use, excluding use in those <18 years of age, between May 16, 2016, and August 1, 2019, at six Ontario tertiary care hospitals. The primary outcome was mortality. The secondary outcomes were in‐hospital arterial thrombotic event (ATE), in‐hospital venous thromboembolism (VTE), length of hospital stay, and length of critical care stay. Results: A total of 85 patients received idarucizumab during the study period for the following indications: 37 (43.5%) for spontaneous bleeding, 28 (32.9%) for traumatic bleeding, 11 (12.9%) for emergency surgeries/procedures, 5 (5.9%) for elective surgeries/procedures, and 4 (4.7%) for other indications. Nineteen patients (22.4%; 95% confidence interval [CI], 14.8%‐32.3%) did not survive their hospitalization. During hospitalization, two patients (2.4%; 95% CI, 0.7%‐8.2%) had ATE, and three patients (3.5%; 95% CI, 1.2%‐9.9%) had VTE. The median length of stay was 8 (interquartile range [IQR], 2.5‐13) days in hospital and 3 (IQR, 2‐5) days in critical care. Conclusions: Compared with clinical trial data, we found a numerically higher rate of mortality and similar rate of ATE and VTE among patients treated with idarucizumab in the real world.